(untitled) (Journal of Parents and Teachers, 2014)
Language or logic mathematic expression is with us in our daily lives and also with the little kids and it cannot be detached. Its application will be used in daily activities and situations. The author explains how collections, activities and exercises contribute to work with maths from the maths corner in the kinder garden class.